ответ:
d=b^2-4ac=(-1)^2-4*1*(-72)=1+288=\sqrt{289}
289
=17
х1=\frac{-b- \sqrt{d} }{2a} = \frac{1-17}{2} = \frac{-16}{2} =-8
2a
−b−
d
=
2
1−17
=
2
−16
=−8
х2=\frac{-b+ \sqrt{d} }{2a} = \frac{1+17}{2} = \frac{18}{2} = 9
2a
−b+
d
=
2
1+17
=
2
18
=9
ответ: -8 и 9
d=b^2-4ac=7^2-4*(-4)*(-3)=49-48=\sqrt{1} =1
1
=1
х1=\frac{-b- \sqrt{d} }{2a} = \frac{-7-1}{2*(-4)} = \frac{-8}{-8} =1
2a
−b−
d
=
2∗(−4)
−7−1
=
−8
−8
=1
х2=\frac{-b+ \sqrt{d} }{2a} = \frac{-7+1}{(-8)} = \frac{-6}{-8} =0,75
2a
−b+
d
=
(−8)
−7+1
=
−8
−6
=0,75
А) 19,5
Б) -26,5
Объяснение:
Б) 8(a+3)-(a-6) = 8a+24-a+6 = 7a+30 при a = -1.5
7*(-1.5)+30 = -10.5+30 = 19.5
В) 3(a-6)-(1-2a) = 3a-18-1+2a = 5a-19 при a = -1.5
5*(-1.5)-19 = -7.5-19 = -26.5